2019
DOI: 10.1088/1361-6560/ab5229
|View full text |Cite
|
Sign up to set email alerts
|

Computational analysis of non-invasive deep brain stimulation based on interfering electric fields

Abstract: Neuromodulation modalities are used as effective treatments for some brain disorders. Non-invasive deep brain stimulation (NDBS) via temporally interfering electric fields has emerged recently as a non-invasive strategy for electrically stimulating deep regions in the brain. The objective of this study is to provide insight into the fundamental mechanisms of this strategy and assess the potential uses of this method through computational analysis. Analytical and numerical methods are used to compute the electr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 39 publications
0
26
0
Order By: Relevance
“…This approach was termed temporal interference (TI) (Grossman et al, 2017) and had been proposed decades earlier under different names, such as interferential current therapy and interferential stimulation (Agharezaee and Mahnam, 2015;Goats, 1990). Translating these pivotal studies into successful clinical therapies requires an understanding of how TI fields are modulated within the human body (Cao and Grover, 2020;Karimi et al, 2019;Rampersad et al, 2019). In consequence, there is an ongoing healthy debate examining the clinical utility of this technology when considering the challenge of inefficient current penetration in large structures, such as the human head (Cao and Grover, 2018; Howell and McIntyre, 2020; Rampersad et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…This approach was termed temporal interference (TI) (Grossman et al, 2017) and had been proposed decades earlier under different names, such as interferential current therapy and interferential stimulation (Agharezaee and Mahnam, 2015;Goats, 1990). Translating these pivotal studies into successful clinical therapies requires an understanding of how TI fields are modulated within the human body (Cao and Grover, 2020;Karimi et al, 2019;Rampersad et al, 2019). In consequence, there is an ongoing healthy debate examining the clinical utility of this technology when considering the challenge of inefficient current penetration in large structures, such as the human head (Cao and Grover, 2018; Howell and McIntyre, 2020; Rampersad et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, because different neurons have different excitability, the interaction between these neurons and extracellular stimulation is complex. Therefore, the biological mechanism of neuroregulatory methods such as tACS is not completely clear (Cubo et al, 2018 ), and many factors need to be analyzed to understand the effect of a given brain stimulation approach (Karimi et al, 2019 ). Therefore, this section summarizes the computer simulation results of electrode parameters, high-definition electrical stimulation, and interference modulation stimulation.…”
Section: Computer Stimulationmentioning
confidence: 99%
“…Studies have shown that only focus montages such as circular montages or high-definition montages can specifically manipulate the phase relationship between two target regions without injecting unwanted electric fields into other regions (Saturnino et al, 2017 ; Karabanov et al, 2019 ). Moreover, the more electrode pairs there are, the more the activation region can be targeted accurately (Karimi et al, 2019 ). Compared with the classical electrode montage, the ring electrode montage can stimulate the target region more intensively and significantly reduce neurosensory side effects (Heise et al, 2016 ).…”
Section: Computer Stimulationmentioning
confidence: 99%
“…Second, by a simple electrostatic analysis, it can be shown that the ED )(bold-italicr vanishes on the y ‐axis. Thus EAMy^ )(yy^= ||k=1Nakϕk )(y where ϕkk=1N can be obtained from the classic modal solution of (1 ) based on the methods of separation of variables, as reported in [20 ]. Noting that all of the quantities in (4 ) are real‐valued, minimising (maximising) of (4 ) is equivalent to minimising (maximising) of false∑k=1Nakϕk )(y2.…”
Section: Analytical Solution To Extended Problemmentioning
confidence: 99%
“…To date, no regularised procedure is introduced to focus the amplitude‐modulated (AM) electric field at the desired location even from the mathematical standpoint at the simulation level. In [20 ], some algorithms were developed to precisely locate the activated region in a homogeneous brain model for TI electrical fields produced by two and four electrode pairs. Though, they have not proposed any solution to increase the spatial resolution.…”
Section: Introductionmentioning
confidence: 99%